Giant viable isolated hydatid cyst of lung and liver with successful surgical outcome in rural setup: a case report - Goel, Tushar; Sharma, Ankit; Dwivedi, Sankalp; Singal, Sameer (International Surgery Journal, 2017)
Hydatid disease has been known since the time of Hippocrates. Hydatid disease is a worldwide parasitic infestation caused by Echinococcus Granulosus characterized by cystic lesions mostly in the liver and lungs with fewer in other parts of the body. Patient details were collected by patient’s IPD file. Complete detailed history, patient vitals, haemogram, ABO, with USG abdomen thorax and CECT chest and upper abdomen was done. Post operatively the outcome was followed by USG R/v and Chest X ray. Treatment diagnosis was giant viable hydatid cyst lung and liver. Right thoracotomy with 5th rib cutting incision was given. Cyst was visualized and managed along with repair of bronchopleural fistula. Hydatid liver was operated later after 3 weeks as elective Surgery. Post-operative period was uneventful with successful outcome. The case was managed successfully by surgical intervention. Surgery remains the choice of complete evacuation of hydatid cyst. Non-complicated hydatid cysts have a good prognosis regardless of their size. Regular follow-up is usually advised to prevent recurrence and spread.